Evaluation of maximum thigh angular acceleration during the swing phase of steady-speed running - Clark, K. P.; Ryan, L. J.; Meng, C. R.; Stearne, D. J. (Sports Biomechanics, 2024)
The hip joint and surrounding musculature must generate and withstand torque during the swing phase of running. Prior research has demonstrated that sagittal plane hip torque increases with speed, indicating that thigh angular acceleration likely increases in a similar manner and may be an important gait parameter. In this investigation, we modelled thigh angle vs. time data with a sine wave function, requiring inputs of thigh angular amplitude and stride frequency. This enabled a simple formula to model maximum thigh angular acceleration (amax, rad/s2) during the swing phase of steady-speed running. A total of 40 participants (20 male, 20 female) completed submaximal and maximal 40 m running trials (n = 154 trials, speed range: 3.1-10.0 m/s), with kinematic data collected from 31-39 m. Thigh angle vs. time curves were well fit by a sine wave function (mean R2 > 0.94 across all trials) and modelled amax was highly correlated with top speed (R2 = 0.81, p < 0.001). We conclude that thigh angular acceleration is an important parameter when examining running performance across a range of speeds and the simple method introduced here to model amax may have practical utility for future examinations into high-speed running mechanics.